PKM Edukasi Pemilahan Sampah untuk Anak TK Unyil Makassar dalam Mewujudkan Lingkungan Bersih Sejak Dini - Jessica, Jessica; Evelyn, Evelyn; Djuranovik, Evelyn; Chandra, Steven Christian; Mustikarini, Carolina Novi (Abdimas Universal, 2025)
The waste problem in Indonesia has become unavoidable due to the increase in population and daily community activities. In facing this challenge, early education plays an important role in forming positive mindsets and habits regarding waste management. This article presents a community engagement project aimed at educating young children about waste management. Implemented at Unyil Kindergarten, the program consists of interactive sessions and a scrapbook workshop. Results showed enthusiastic participation and understanding among children, highlighting the effectiveness of the interactive approach. Scrapbooking activities serve as a practical evaluation tool, demonstrating children's ability to apply knowledge. This initiative also creates opportunities for parents and teachers to get involved in the learning process, reinforcing concepts taught in the classroom, and extending its positive impact to the home environment and surrounding communities. With a fun and hands-on approach, children not only understand the importance of waste management but also feel motivated to take concrete action in their daily lives. Through collaboration between educational institutions and the community, this project provides a real example of how early education can be the key to forming future generations who care about the environment and have a high awareness of their responsibilities towards this earth.